De klokken van Giessen-Oudekerk en Oosterwijk (Bulletin KNOB, 1993)
In 1542 the church of Giessen-Oudekerk acquired a new clock, which was probably melted down again by the Sea Beggars in 1572. In 1548 the church of Oosterwijk acquired a clock dating from 1502, which had presumably been taken from North France as war booty in 1537.